A robust and efficient calibration method for spot laser probe on CMM. (15th March 2020) - Shen, Yijun; Zhang, Xu; Wang, Zhenyou; Wang, Jianxiang; Zhu, Limin
Highlights: Compared to the existing methods, the proposed method improves the calibration accuracy by 87.1% in the simulation. The proposed method possesses the micron-level accuracy in the real experiment. With the sensitivity analysis, the proposed method proves to be robust under heavy noise. The proposed method is more efficient than the existing methods. The proposed method has universality and it can be applied to the calibration of other displacement sensors. Abstract: Among all the non-contact measurement devices, the spot laser probe achieves a good balance between accuracy and efficiency. When the laser probe is applied to three-dimensional (3-D) measurement, the laser beam direction is essential to transform the probe indication from 1-D distance information into a 3-D vector representing differences in space coordinates. In this article, a calibration method is proposed for the laser probe mounted on the coordinate measuring machine (CMM). During the calibration procedure, the CMM moves along the user-planned path and hundreds of points are scanned in a few seconds. In order to get an accurate laser beam direction estimate, we refine the original inaccurate direction, which is specified by the mechanical structure of the probe fixture, by mapping the scanned points into a sphere. The simulation and experiment manifest that the proposed method is superior to the existing methods and meets the requirement of the micron-level measurement.